Family business - Sharma, Pramodita; Melin, Leif (SAGE library in business and management, 2015)
The last three decades have witnessed a dramatic increase in research on family businesses, as institutions have increasingly recognized that family businesses represent the most common form of business organization and a large part of the GDP in most countries. This major work answers the global need for a resource that captures and presents a comprehensive overview of the literature in the field of family business